(untitled) (Asian Journal of Social Science Studies, 2021)
Research on emotional labor focus on related employees’ work outcomes, well-beings, and dissonances that could be ignored some moderation effects especially between emotional labor and job involvement. This study focused on difference types of PE fit that individual fit takes a moderation role between emotional labor and job involvement. Data from 230 convenience store full time (71.7%) and part time (28.3%) working employees were collected. Results indicate that difference types of PE fit predicated moderating effects influenced the relationship between predictor (emotional labor) and criterion variables (job involvement). In sum, in describing PE fit mediating the relationships between emotional labor and job involvement, Further, we have made the points that (a) emotional labor can indirectly influence job involvement by the mediating processes of perceived person-environment, (b) person-environment fit revealed partially mediating effects on the relationship between emotional labor and job involvement, (c) among emotional labor, PE fit, and job involvement regarding significance positive effects.